GHRH, GH, and IGF-I Basic and Clinical Advances - Blackman, Marc R.; Roth, Jesse; Harman, S. Mitchell; Shapiro, Jay R. (Serono Symposia USA, 1995)
Recent research suggests that adult growth hormone (GH) deficiency, whether of pathological or physiological origin, is associated with a dis tinct syndrome that includes alterations in body composition, endocrine metabolic function, immune competence, and physical and psychosocial well-being. Not surprisingly, substantial investigative effort is currently focused on validating the above hypothesis and on determining whether restoration of a normal GH-IGF-I axis in various states of adult GH deficiency is clinically useful, safe, and cost-beneficial. This book contains the proceedings from the Symposium on GHRH, GH, and IGF-I: Basic and Clinical Advances, held December 9 to 12, 1993, in San Diego, California, and sponsored by Serono Symposia USA, Inc. The conference was meant to highlight selected novel and exciting clinical research developments related to possible therapeutic uses of recombinant human GH and IGF-I, GHRH, GH releasing peptides, and related GH secretagogues. This meeting occurred only one year after a similar Serono symposium that was somewhat more oriented to novel basic science discoveries, thus attesting to the current scientific and clinical interest in this area